Pelatihan Pembentukan Karakter Berorganisasi Bagi Mahasiswa - Yolanda, Fitriana; Dahlia, Agus; Nofera, Nurmahya Dini (Community Education Engagement Journal, 2019)
His service aims to improve the knowledge and insight of Gema Kosgoro (Kosgoro Student Movement) Pekanbaru city Tangkerang Labuai Village, Bukit Raya District, Pekanbaru city in organizing and giving opportunities to Gema Kosgoro (Kosgoro Student Movement) Pekanbaru city to be motivated to participate in organizing through training organizational character formation. The target to be achieved is to provide knowledge and insight on the formation of organizational character through training and provide motivation so that students can play an active role in the organization. To achieve these objectives, the number of trainees to play an active role and to provide training materials is to establish organizational character for students